Sensitivity to Envelope Interaural Time Differences at High Modulation Rates - Monaghan, Jessica J. M. (Trends Hear, 2015)
Sensitivity to interaural time differences (ITDs) conveyed in the temporal fine structure of low-frequency tones and the modulated envelopes of high-frequency sounds are considered comparable, particularly for envelopes shaped to transmit similar fidelity of temporal information normally present for low-frequency sounds. Nevertheless, discrimination performance for envelope modulation rates above a few hundred Hertz is reported to be poor—to the point of discrimination thresholds being unattainable—compared with the much higher (>1,000 Hz) limit for low-frequency ITD sensitivity, suggesting the presence of a low-pass filter in the envelope domain. Further, performance for identical modulation rates appears to decline with increasing carrier frequency, supporting the view that the low-pass characteristics observed for envelope ITD processing is carrier-frequency dependent. Here, we assessed listeners’ sensitivity to ITDs conveyed in pure tones and in the modulated envelopes of high-frequency tones. ITD discrimination for the modulated high-frequency tones was measured as a function of both modulation rate and carrier frequency. Some well-trained listeners appear able to discriminate ITDs extremely well, even at modulation rates well beyond 500 Hz, for 4-kHz carriers. For one listener, thresholds were even obtained for a modulation rate of 800 Hz. The highest modulation rate for which thresholds could be obtained declined with increasing carrier frequency for all listeners. At 10 kHz, the highest modulation rate at which thresholds could be obtained was 600 Hz. The upper limit of sensitivity to ITDs conveyed in the envelope of high-frequency modulated sounds appears to be higher than previously considered.